2018
DOI: 10.1080/20008198.2018.1425576
|View full text |Cite
|
Sign up to set email alerts
|

A socio-interpersonal approach to adjustment disorder: the example of involuntary job loss

Abstract: Background: Adjustment disorder (AjD) was redefined for ICD-11 with core symptoms of preoccupation with a stressor and failure to adapt. The socio-interpersonal framework model for stress-response syndromes suggests that interpersonal factors, besides intrapersonal processes, substantially contribute to the development of AjD. Objective: The current study aimed to identify predictive factors in the development of AjD symptoms by the application of a framework model for stress-response syndromes. Method: N = 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 53 publications
4
33
1
1
Order By: Relevance
“…Knowledge about the predictors or risk factors of ICD-11 adjustment disorder is lacking. Previous studies found that adjustment disorder may be associated with various life-stressors (Lorenz et al, 2018a;Zelviene et al, 2017), exposure to trauma (O'Donnell et al, 2016;Ring et al, 2018), demographic characteristics and sociointerpersonal factors (Horn & Maercker, 2016;Lorenz et al, 2018aLorenz et al, , 2018b. In a community sample of survivors from terror attack in Israel it was found that previous traumatic experiences, stressful events and younger age were significant predictors associated with ICD-11 adjustment disorder symptoms, whereas physical proximity to the site of the terror attack and gender were not (Mahat-Shamir et al, 2017).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Knowledge about the predictors or risk factors of ICD-11 adjustment disorder is lacking. Previous studies found that adjustment disorder may be associated with various life-stressors (Lorenz et al, 2018a;Zelviene et al, 2017), exposure to trauma (O'Donnell et al, 2016;Ring et al, 2018), demographic characteristics and sociointerpersonal factors (Horn & Maercker, 2016;Lorenz et al, 2018aLorenz et al, , 2018b. In a community sample of survivors from terror attack in Israel it was found that previous traumatic experiences, stressful events and younger age were significant predictors associated with ICD-11 adjustment disorder symptoms, whereas physical proximity to the site of the terror attack and gender were not (Mahat-Shamir et al, 2017).…”
Section: Introductionmentioning
confidence: 89%
“…In the context of involuntary job loss, ICD-11 adjustment disorder was associated with greater age, lower financial household budget, and exposure to multiple stressors and workrelated factors (Perkonigg et al, 2018). Interpersonal factors, such as higher loneliness, higher dysfunctional disclosure, and lower self-efficacy were associated with higher adjustment disorder symptom severity and a higher likelihood of meeting the diagnostic criteria for ICD-11 adjustment disorder (Lorenz et al, 2018a).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…control group, they have fewer individual characteristics like self-acceptance, self-confidence, goal setting, empathy, helpfulness, hopefulness about the future, and social interaction, so that they are not very capable of coping with stressful situations. Lorenz et al(32) ve Oh et al(33) similarly reported that patients with adjustment disorder were not very successful at coping with stress.…”
mentioning
confidence: 99%